Apparent Emotional Expression Explains the Effects of Head Posture on Perceived Trustworthiness and Dominance, but a Measure of Facial Width Does Not. (April 2020) - Zhang, Dongyu; Lin, Hongfei; Perrett, David I.
Interpreting the personality and the disposition of people is important for social interaction. Both emotional expression and facial width are known to affect personality perception. Moreover, both the apparent emotional expression and the apparent width-to-height ratio of the face change with head tilt. We investigated how head tilt affects judgements of trustworthiness and dominance and whether such trait judgements reflect apparent emotion or facial width. Sixty-seven participants rated the dominance, emotion, and trustworthiness of 24 faces posing with different head tilts while maintaining eye gaze at the camera. Both the 30° up and 20° down head postures were perceived as less trustworthy and more dominant (less submissive) than the head-level posture. Change in perceived trustworthiness and submissiveness with head tilt correlated with change in apparent emotional positivity but not change in facial width. Hence, our analysis suggests that apparent emotional expression provides a better explanation of perceived trustworthiness and dominance compared with cues to facial structure.